1993
DOI: 10.1113/expphysiol.1993.sp003683
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and voluntary contraction on presynaptic inhibition of soleus muscle Ia afferent terminals in man

Abstract: SUMMARYTransmission in a pathway mediating presynaptic inhibition of soleus I a afferent terminals was assessed from the reduction of soleus muscle H reflex amplitude brought about by a short conditioning vibration pulse applied to the anterior tibialis muscle. In a group of young subjects (aged between 21 and 37 years) the mean reduction in reflex size with the limb relaxed was to 29-2 % of control, whereas in a group of older subjects (aged between 59 and 74 years) the reduction was significantly less, to 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 15 publications
3
29
3
5
Order By: Relevance
“…The decrease in presynaptic inhibition of Ia afferents during the position task in young adults is consistent with previous results from our laboratory (Baudry and Enoka 2009). The present findings, however, did not show any change in the amount of Ia presynaptic inhibition during contractions performed at 5, 10, and 15% MVC force, which contrasts with previous studies that have found a decrease in the amount of Ia presynaptic inhibition in the soleus muscle with an increase in contraction strength of the plantarflexor muscles (Butchart et al 1993;Earles et al 2001). The divergent findings are likely attributable to differences in how the target torque was determined for each contraction: Earles et al (2001) used the amplitude of the surface EMG to set the intensity of the contraction, whereas Butchart et al (1993) used the same absolute torques across subjects.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The decrease in presynaptic inhibition of Ia afferents during the position task in young adults is consistent with previous results from our laboratory (Baudry and Enoka 2009). The present findings, however, did not show any change in the amount of Ia presynaptic inhibition during contractions performed at 5, 10, and 15% MVC force, which contrasts with previous studies that have found a decrease in the amount of Ia presynaptic inhibition in the soleus muscle with an increase in contraction strength of the plantarflexor muscles (Butchart et al 1993;Earles et al 2001). The divergent findings are likely attributable to differences in how the target torque was determined for each contraction: Earles et al (2001) used the amplitude of the surface EMG to set the intensity of the contraction, whereas Butchart et al (1993) used the same absolute torques across subjects.…”
Section: Discussioncontrasting
confidence: 56%
“…The present findings, however, did not show any change in the amount of Ia presynaptic inhibition during contractions performed at 5, 10, and 15% MVC force, which contrasts with previous studies that have found a decrease in the amount of Ia presynaptic inhibition in the soleus muscle with an increase in contraction strength of the plantarflexor muscles (Butchart et al 1993;Earles et al 2001). The divergent findings are likely attributable to differences in how the target torque was determined for each contraction: Earles et al (2001) used the amplitude of the surface EMG to set the intensity of the contraction, whereas Butchart et al (1993) used the same absolute torques across subjects. Accordingly, Meunier and Pierrot-Deseilligny (1998) reported no change in the amount of soleus Ia presynaptic inhibition across different contraction intensities when the target torque was set relative to the MVC torque (12, 25, and 50% MVC force).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Therefore, the impact of the afferent feedback on the agonist and antagonist motor neuron populations is reduced, although it is possible that an increased gamma drive may increase spindle output and thereby in part compensate for the decreased synaptic gain (Llewellyn et al 1990;. Baudry et al (2010) showed that young subjects increased the afferent gain when exposed to a more unstable task, whereas older subjects, who are less able to modulate presynaptic inhibition (Butchart et al 1993;Koceja and Mynark 2000), reacted with an increase in the cocontraction level. These observations suggest that cocontraction can be considered a more easily applied strategy that is often the first choice when a subject is exposed to an unknown environment, whereas it is more difficult, but also more desirable because of metabolic costs, to adjust the afferent gains to the appropriate level.…”
Section: Discussionmentioning
confidence: 99%
“…presynaptic mechanism; see Pierrot-Desseilligny and Burke 2005;Stein 1995;Zehr and Stein 1999). A reduced ability to modulate presynaptic inhibition has been indeed suggested in elderly adults (Butchart et al 1993;Earles et al 2001). …”
Section: Age-related Changes In H-reflex Modulationmentioning
confidence: 98%